Green School-Based Institutional Innovation at MI Assunniyyah 45 Kencong, Jember - Dukan Jauhari Faruq; Titiek Rohanah Hidayati; Erma Fatmawati (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This research stems from the importance of developing an environmentally conscious school culture—one that focuses not merely on physical greening activities but also on institutional innovations capable of ensuring the sustainability of environmental programs within the madrasah (Islamic school). The Adiwiyata program, as a form of the "Green School" initiative, requires policy support, human resource management, and sustainability systems integrated into the madrasah's organizational culture. This study aims to describe and analyze Green School-based institutional innovations at MI Assunniyyah 45 Kencong, Jember, covering policy and strategic planning, human resource organization, and program sustainability systems. A qualitative approach was employed, utilizing a descriptive-interpretative research design. Data were collected through interviews, observations, and documentation. The research subjects included the madrasah principal, teaching staff, and students. Data analysis followed the Miles, Huberman, and Saldana model, comprising data reduction, data display, and conclusion drawing. Data validity was verified through source and technique triangulation. The findings indicate that Green School-based institutional innovation is realized through: (1) environmentally conscious policies integrated into the madrasah's vision, budgeting, curriculum, participatory activities, and the management of eco-friendly facilities; (2) the establishment of a specific organizational structure—a working group—that systematically involves teachers and students in environmental program management; and (3) the strengthening of an environmental culture through the integration of learning, extracurricular activities, the use of school grounds as a learning medium, stakeholder participation, and the cultivation of environmentally conscious character traits. The study concludes that the Adiwiyata program at MI Assunniyyah 45 Kencong, Jember, has evolved into an institutional innovation integrated into all aspects of madrasah life, fostering a sustainable Green School culture grounded in Islamic values.